AS POLÍTICAS PÚBLICAS NA PERSPECTIVA DA DESIGUALDADE NO NOROESTE COLONIAL GAÚCHO - Allebrandt, Sergio L.; Siedenberg, Dieter R.; Tenorio, Fernando G.; Ceratti, Larissa L.; Filho, Carlos J. M.; Dallepiane, Claudia W. S.; Dallepiane, Sabrina (Salão do Conhecimento, 2013)
Resumo